DEVELOPMENT OF MOON ORCHID (Phalaenopsis amabilis L.) TISSUE CULTURE MODULE AS TEACHING MATERIALS FOR BIOLOGICAL EDUCATION - Mellisa Mellisa; Sri Amnah (Jurnal Pelita Pendidikan, 2021)
The module is one of the alternative teaching materials that can help students or educators in the learning and teaching process. This study aims to examine the validity of the tissue culture module of the moon orchid (Phalaenopsis amabilis L.) using leaf explants and the hormone Naphthalene Acetic Acid (NAA), which was developed at the Biology Faculty of the Islamic University of Riau. This study uses the ADDIE model with several stages: analysis, design, and development. These research results are a printed product, namely a tissue culture module. This research data was obtained from the validation results by material experts, learning experts, and response tests with lecturers and 16 2015 school year students who had taken the tissue culture course. The validation results by material experts showed that the module developed got an average percentage of 86.45% (very valid). Learning experts got an average percentage of 87.74% (very valid). This developed module received very valid responses from lecturers and students. It can be seen from the average response of lecturers 95.48% (very good) and students with an average percentage of 90.31% (very good). Based on the validation results from the experts, the product in the form of a tissue culture module is very valid to be used in the learning process.